Reclaiming Your Time: Tools From Culturally Responsive Pedagogy (CRP) for Making General Interventions Local. Issue 3 (3rd July 2019) - McGregor, Kristidel; Belcher, Deanna Chappell; Fitch, Katie S.
Abstract: In the last 20 years, teachers have been placed in an impossible bind: we know that classrooms are situated in geographic and sociohistorical contexts, but we are required to implement one-size-fits-all interventions. In this article, three classroom teachers turned teacher educators share ideas for how to use culturally responsive pedagogy to align mandated interventions to the needs of students. We share our own stories as examples of how these principles look in practice in classroom communities.